Prevalence of lower urinary tract symptoms (LUTS)among young age medical population - Nusee, Zalina (Faculty of Medicine, International Islamic University Malaysia, 2011)
Introduction: Frequency of lower urinary tract symptoms (LUTS) in young age women is not well studied. It is said to be common among female elderly and multiparous opulation. The aim of this study is to obtain the prevalence of LUTS among nulliparous students in relation to their personal hygiene. Materials and methods: This is a prospective cross-sectional study conducted among 200 nulliparous medical and nursing students aged between 18-28 years using standardized questionnaires. Urine samples were also collected from students to detect urinary tract infections. Results: The complete data sets of 146 students were analyzed. All of them were nulliparous, single and not sexually active. The prevalence of LUTS was 52.7% consist of over-active bladder, urinary incontinence (UI) and voiding difficulty respectively (51.3%, 34.9% and 45.2%). The most common type of UI was stress urinary incontinence which was 21.9% followed by 11.6% of urgency incontinence. Conclusion: The prevalence of LUTS among young age population is high at 52.7%. Public awareness regarding LUTS and availibility of treatment is needed.